Entrepreneurial opportunity recognition in the face of disasters. Issue 4 (19th March 2020) - Gur, Furkan Amil; Bendickson, Joshua S.; Madden, Laura; McDowell, William C.
Abstract : Purpose: Disasters drastically affect regional industries; consequently, the study of regional resilience is of much interest to organizational researchers. To that end, this study examines the role of entrepreneurial opportunity recognition, stakeholder engagement, and elements of psychological recovery in the US Gulf Coast following the Deepwater Horizon oil spill of 2010. Design/methodology/approach: Through a qualitative content analysis of 183 industry-relevant articles published during and after the disaster, this study unpacks the most significant themes at work in the recovery process, including the psychological elements of the oil spill and its aftermath, the role of various internal and external stakeholders, and emerging opportunities for entrepreneurial activity in the region for regional resilience and recovery. Findings: The nine themes that emerged from the data were captured in three categories mapped over time. Category one, psychogical states during and after the oil spill, include denial, coping, and recovery. Category two, regional recovery efforts and the role of stakeholders, includes the themes distractions, bargains, and material support. Category three, emerging opportunities, includes financial support, new markets, and reparations. Originality/value: By mapping these themes over distinct time periods, this study identifies and explores patterns in the recovery period and use them to draw theoretical and practical implications.